An exploratory study of gender segregation in investment management in Ireland - Sheerin, Corina (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2013)
Despite the entry of women in recent years, Investment Management remains a male domain. The absence of women is most notable in the fund management suite and on the trading floor (the most lucrative sub sectors of the industry) where "a jungle of chest-pounding males" prevails (Lewis 1989, p.9). This research addresses the factors that influence men and women to embark on careers in Investment Management as well as those barriers that are faced once inside the sector. Perceptions and experiences of potential entrants to the sector, as well as those of people who work in the sector, are examined to identify barriers, both perceptual and real, facing women. The research strategy involved a mixed method approach using focus groups, a questionnaire survey and semi-structured interviews to provide a holistic understanding of relevant ideologies and practices to explain the male-domination of the sector.
Keywords: Statistics, Ph.D.; Ph.D. Trinity College Dublin